Legal truth and discourses of violence in Post-apartheid Commissions of Inquiry: The TRC and Marikana Commission - Lester, Claire-Anne Louise (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.